Increase in Relative Abundance and Size of Snapper Chrysophrys auratus Within Partially-Protected and No-Take Areas in a Temperate Marine Protected Area - Harasti, David; Williams, Joel; Mitchell, Emma; Lindfield, Steven; Jordan, Alan (Frontiers in Marine Science, 2018)
Marine Protected Areas (MPAs) are known to contribute towards the conservation of marine biodiversity, particularly targeted fishery species. Snapper Chrysophrys auratus are an important recreational and commercial fish species in New South Wales (NSW), Australia, and despite fishery management for this species, they are considered ‘growth overfished’ in this region. To assess how C. auratus respond to the implementation of an MPA with several no-take and partially protected areas in temperate NSW, we monitored their populations over a decade (2006-2017) using baited remote underwater video systems (BRUVs). Surveys were conducted in the Port Stephens-Great Lakes Marine Park with BRUVs deployed on rocky reefs in depths of 20 – 50 m. Long term seasonal sampling (winter vs summer) was undertaken at two locations (Broughton and Fingal Island), and changes in C. auratus abundance prior to, and eight years after zoning implementation, were assessed between these two locations. In total, we sampled five no-take areas within the marine park and five comparative nearby partially protected fished areas and three sites located outside the marine park boundaries. The most pronounced changes in abundance and size structure for C. auratus were observed in the Broughton Island no-take area where numbers increased almost 3-fold (2.91 times) over 8 years of protection. Relative abundance showed seasonal variation at two locations, and we consistently recorded increasing abundance within no-take areas at Broughton and Fingal Island compared to nearby sites open to fishing. Surveys across the five no-take areas found a significant increase in the abundance of C. auratus, whilst the five partially-protected locations in the marine park still recorded higher abundances than sites outside the marine park. In addition, length measurements from stereo-BRUVS indicated that C. auratus were significantly larger in no-take areas compared to partially-protected areas in the marine park and sites outside the marine park. This study demonstrates how the implementation of the marine park and the protection afforded by no-take and partially-protected areas provides refuge for this important fishery targeted species.